Pathologies of Calcium Channels - Weiss, Norbert; Koschak, Alexandra (Springer Berlin Heidelberg : Imprint: Springer, 2014)
Calcium ions represent Mother Nature's 'ion-of-choice' for regulating fundamental physiological functions, as they initiate a new life at the time of fertilization and guide subsequent developmental and physiological functions of the human body. Calcium channels, which act as gated pathways for the movement of calcium ions across the membranes, play a central part in the initiation of calcium signals, and defects in calcium channel function have been found to result in a plethora of human diseases, referred to as the calcium channelopathies. Pathologies of Calcium Channels brings together leading international experts to discuss our current understanding of human diseases associated with the various calcium channels, from their molecular basis to potential future therapeutic targeting of calcium channels.